Sustainability in aviation : Views of external stakeholders on environmental sustainability in the commercial airline industry - Saramola, Henna (My University, 2023)
Environmental sustainability has gained increasingly attention in the aviation industry since the 1990s. The attention is justified as aviation industry contributes 2% of all yearly CO2 emissions. As the industry is still heavily reliant on the use of fossil fuels the amount of emissions increases with the growth of the industry. Aviation has become a crucial part of global business, but the yearly growth rate is not ecologically sustainable. Coherent actions from all stakeholder groups is needed to solve the challenges that aviation causes to the environment. This research was conducted to analyse the views of external stakeholder groups of airlines in terms of environmental sustainability in the aviation industry. The research follows the research design of a qualitative single case study with an interpretive approach. The theoretical framework of the research is bult on triple bottom line approach together with stakeholder theory. Expert interviews and a group interview of customers were used to collect the empirical data from four different external stakeholder groups. The collected data was analysed and combined with the theoretical framework to understand the views of external stakeholder groups on environmental sustainability in the aviation industry and create suggestions how these views can be utilized to support the development of environmental sustainability. The following findings were made: External stakeholder groups view the environmental challenges that are created by aviation as pressing and important to solve. There are knowledge caps on the matter which can create suspicions towards the current operations to handle the challenges. External stakeholder groups found it hard to see their own power compared to the airlines in promoting environmental sustainability. For utilization of the knowledge and views of the external stakeholder groups, airlines should aim towards open and honest communication to diminish the risk of greenwashing and knowledge sharing should be encouraged between the stakeholder groups.

Ympäristövastuullisuuteen liittyvät kysymykset ovat keränneet kasvavissa määrin huomiota ilmailualalla viime vuosikymmenien aikana. Huomio ei ole ollut turhaa, sillä ilmailu tuottaa 2 % vuosittaisista hiilidioksidipäästöistä. Ilmailuala on edelleen vahvasti riippuvainen fossiilisista polttoaineista, jonka myötä alan kasvu lisää suoraan ympäristölle haitallisten päästöjen määrää. Ilmailuala on globaalille liiketoiminnalle elintärkeä ajuri, mutta alan vuosittainen kasvu luo huomattavia haasteita ympäristölle. Yhtenäisiä toimia eri sidosryhmiltä tarvitaan, jotta tilanteeseen pystytään puuttumaan. Tämän tutkimuksen tarkoitus on selvittää lentoyhtiöiden eri ulkoisten sidosryhmien näkemyksiä ilmailualan vastuullisuuteen liittyen. Tutkimus tehtiin laadullisena tapaustutkimuksena, jossa hyödynnettiin tulkitsevaa lähestymistapaa. Tutkimuksen teoreettinen viitekehys pohjautuu sidosryhmäteoriaan ja vastuullisuuskirjallisuuteen. Empiirinen aineisto kerättiin asiantuntija- ja ryhmähaastatteluilla, jossa haastateltiin neljää eri ulkoista sidosryhmää. Aineistoa peilattiin tutkimuksen teoreettiseen viitekehykseen tavoitteena ymmärtää ulkoisten sidosryhmien näkemyksiä ilmailualan ympäristövastuullisuudesta ja luoda ehdotuksia, kuinka lentoyhtiöt voivat hyödyntää näitä näkemyksiä ympäristövastuullisuuden kehittämisessä. Tutkimuksen perusteella tehtiin seuraavia löydöksiä: Ulkoiset sidosryhmät näkevät ympäristövastuullisuuteen liittyvät haasteet todellisina ja tärkeinä ratkaista, jotta lentoliikenne voisi tulevaisuudessa olla kestävämpää. Sidosryhmien tiedon määrässä ilmailuun liittyvässä ympäristövastuullisuudessa on eroja, jotka saattavat luoda epäluuloista suhtautumista lentoyhtiöiden ilmastotoimia kohtaan. Ulkoiset sidosryhmät näkivät oman roolinsa haasteellisena ja pienempänä ympäristöhaasteiden ratkaisussa verrattuna muihin sidosryhmiin tai lentoyhtiöihin. Löydösten perusteella päästiin seuraaviin johtopäätöksiin: lentoyhtiöt pystyvät hyödyntämään eri sidosryhmien näkemyksiä ja tietoa aiheesta, tulee kommunikaatio sidosryhmien kanssa olla avointa ja tiedonvaihtoa eri sidosryhmien välillä tulee tukea.
Keywords: aviation, commercial airlines, environmental sustainability, external stakeholder groups, triple bottom line approach, stakeholder theory, ilmailuala, lentoyhtiöt, ympäristövastuullisuus, ulkoiset sidosryhmät, sidosryhmäteoria, kolmoistilinpäätös